Exploring the antibacterial potential of Clidemia hirta leaf extract against the pathogenicity of Pseudomonas aeruginosa: in vitro and in silico approaches - Murugesan, Vignesh; Palanivel, Pargovan; Ramesh, Gokul; Ganesh, Dwarakesh; Michael, Helan Soundra Rani; Bandhumy Lingam, Shivakumar; Sivaraman, Rathish Kumar (Frontiers in Pharmacology, 2025)
BackgroundMultidrug-resistant bacterial pathogen P. aeruginosa has emerged as a significant global health challenge, underscoring the urgent need to identify and develop alternative therapeutic agents including plant natural products. In this study, the extract from Clidemia hirta plant extract was analyzed for antibacterial properties against Pseudomonas aeruginosa and component composition.Material and MethodsThe plant extract was obtained from leaves of C. hirta and its antibacterial activity against P. aeruginosa was determined in Kirby-Bauer disc diffusion assay. In this assay, the activity of the extract was tested at two different concentrations of 50 and 100 μg/mL. The minimum inhibitory concentration (MIC) of the extract against P. aeruginosa was used with its MIC values against Vero cells to determine the selectivity index. GC-MS determined the phytochemical composition of the plant extract. The property of different extract components to bind the target receptor Penicillin Binding Protein 2a (7KIS) was assessed in silico studies including docking and molecular dynamics (MD) analyses. In these analyses, the stability and interaction dynamics of the Penicillin Binding Protein 2a (7KIS) protein complexed with selected extract components.ResultsThe plant extracts had antibacterial activity against P. aeruginosa, with inhibition zones measuring 13 mm and 19 mm for 50 and 100 μg/mL concentrations, respectively. The MIC of the plant extract was determined to be 20 μg/mL, while its selectivity index was 4.54, indicating its antibiotic potential. One extract component, 2, 4-di-tert-butylphenol compound holds a binding affinity of −6.2 kcal/mol in molecular docking studies. MD simulations revealed stable binding interactions between the 7KIS protein and the tested ligands, characterized by reduced atomic fluctuations and energetically favorable binding profiles.ConclusionThis study showed that C. hirta extract has a robust antibacterial potential against P. aeruginosa. Furthermore, GC-MS profiling molecular docking, and dynamic simulation data showed that such antibacterial potential might be attributed to its one component, 2, 4-di-tert-butylphenol. Further, in vivo and in vitro studies are needed to show the applicability of bioactive compounds from C. hirta in combating resistant bacterial pathogens.